Technological support in the process of interaction of the psychologist and the special teacher - Kukushkina, Olga (Social Welfare: Interdisciplinary Approach, 2011)
Developmental psychology does not provide desirable results in the development of a child with special needs in the process of his or her education if the teacher does not come together with the psychologist in revealing and removing disbalance between education and development of each child. In this report the unconventional approach to use of computer technologies to support the process of interaction of the psychologist and the teacher has been considered – the “dialogue” on the problem of the relation of education and development of a child with the special needs.Developing and diagnostic computer environment “World through your window” has been created, which is special educational tools with the following functions: To make “visible” the problems of child development that are hidden in conventional education; To show how to transform the selected problems of child development into the special tasks of his/her education; To show how to correlate “steps” in child development to “steps” in a teacher’s technique.The report shows how to use this kind of special tools for revealing and removing disbalance between education and reading development of a child.
Keywords: computer technologies; educational tools; special needs; reading development